Field notes contributed by Dennis Thompson, spring 1996 - Thompson, Denniset al (1996)
Spring report of birds found in central Iowa contributed by Dennis Thompson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed/flatbed